P197 Does being an immigrant affect work disability duration for injured workers in canada?. (1st September 2016) - Saffari, Niloufar; McLeod, Chris; Koehoorn, Mieke; McGrail, Kimberlyn
Abstract : Objective: To investigate whether disability durations differ by immigration status for injured workers with a workers' compensation claim. Method: A cohort of injured workers with an accepted workers' compensation claim from 1995 to 2012 was derived from workers' compensation claim records and linked to Citizenship and Immigration Canada Permanent Residents data. Injured workers were identified as recent immigrants (less than10 years in Canada), established immigrants (10 years or more in Canada), and Canadian-born workers. Disability duration was derived from claim data that indicated the number of disability days paid in the first year after injury. Differences in disability duration by immigration status were examined at different points across the disability duration distribution at the 25th, 50th and 75th percentiles, using quantile regression. Models were stratified by age and sex, and where appropriate, adjusted for age, sex, and occupation. Results: Both recent and established immigrants had longer work disability durations than Canadian-born workers, at all points of the distribution (Recent: 25th % 0.5 days, 0.4–0.6; 50th %, 1.8 days, CI: 1.6–2; 75th %, 3.9 days, CI: 3.1–4.7; Established: 25th % 0.9 days, 0.8–1; 50th% 3; CI: 2.8–3.3; 75th % 6.6 days, 5.6–7.5). For younger immigrants, the effect was greater (Recent: 75th %, 7 days, CI: 6–7.9; Established: 12 days, CI: 9.2–14.8) than at older ages (Recent: 1.3 days, CI: −0.2–2.5; Established: 6 days, CI: 5–7.3). The effect was different for immigrant women (Recent: 75th%, −1.5 days; CI: −3.1–0.01; Established: 6.4 days; CI: 4.8–8.1) than immigrant men (Recent: 75th%, 5.8 days, CI: 4.9–6.8; Established: 6.4 days; CI: 5.2–7.6) in sex-stratified models. Conclusion: Immigrants, especially established immigrants, have longer disability durations than Canadian-born workers, following a work injury. Results show that immigrants may face barriers after work injury, which persist even for established immigrants. Future research may need to focus on interventions to reduce this inequality.